2012
DOI: 10.1002/psp.1752
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐European Student Mobility and European Identity: A Successful Marriage?

Abstract: Studies on European identity generally focus on elites, even though processes of identity formation may also take place in other societal domains. As one of the underlying rationales of European student exchange programmes is the promotion of European citizenship, I examine empirically the influence of European student mobility on European identity. The analysis is based on a mixed‐method approach. The quantitative element consists of an online survey at nine universities in Austria, Belgium, Italy, Norway, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 44 publications
3
64
0
2
Order By: Relevance
“…After all, research into European identity formation among young individuals in international settings confirmed that social interaction plays an important role in the development of such identities (see for example Van Mol, 2013;Savvides, 2006). As bi-national couples are continuously exposed to 'European otherness' in their relationship, it is imaginable they dialectically negotiate their identification schemes.…”
Section: European Identity Transnational Solidarity and Intermarriagesmentioning
confidence: 99%
See 1 more Smart Citation
“…After all, research into European identity formation among young individuals in international settings confirmed that social interaction plays an important role in the development of such identities (see for example Van Mol, 2013;Savvides, 2006). As bi-national couples are continuously exposed to 'European otherness' in their relationship, it is imaginable they dialectically negotiate their identification schemes.…”
Section: European Identity Transnational Solidarity and Intermarriagesmentioning
confidence: 99%
“…These variables were included since findings from studies investigating the relationship between international experiences -mainly the Erasmus programme -and European identification, were mixed (e.g. King and Ruiz-Gelices, 2003;Kuhn, 2012;Sigalas, 2010;Van Mol, 2013;Mitchell, 2014 Table 2 provides a descriptive overview of the dependent variables in the analysis by union type. As can be seen noted, there seems to exist a difference in identification as a European between individuals in a uni-national and those who in a bi-national relationship, with those in a bi-national union scoring higher.…”
Section: Control Variablesmentioning
confidence: 99%
“…Previous work has emphasized the economic or social impacts of EU funds in a narrow mode (Bachtler & Gorzelak, 2007;Mitchell, 2015). Only in a tangential and programspecific fashion, or as part of larger studies incorporating independent variables beyond EU funds have scholars explored the relationship between budgetary dynamics and institutional legitimacy (Eichenberg & Dalton, 1993;Van Mol, 2013). EU funds could be considered worthwhile if they contribute to the legitimacy of either associated institutions or the organization in general, which it appears they might.…”
Section: Discussionmentioning
confidence: 99%
“…One example is the academic debate about the impact of the Erasmus program, a transnational exchange arrangement for students (Mitchell, 2015;Van Mol, 2013). Here the focus has been on assessing whether the introduction of young persons to other cultural environments promotes the creation and development of a European identity (Mitchell, 2015;Sigalas, 2010).…”
Section: The Efficacy Of Eu Fundsmentioning
confidence: 99%
“…Within current mobility studies (Cresswell, 2006;Urry, 2007), there is already a large literature addressing international migration and mobility in Europe from a multiplicity of perspectives (Jensen and Richardson, 2004;Benhabib and Resnik, 2009;Jensen, 2013), and an emerging literature addressing EU in-mobility from several disciplines (mainly from economics, demography, sociology, and politics); but there is perhaps less analysing it in the context of the current economic and financial crisis and the last processes of EU enlargement. See, among the most recent: Ackers and Gill (2009), Dobson (2009), Fassmann et al(2009, Balan and Uzlau (2010), Black et al (2010), Collet (2012), Bertoli et al, (2013), Currie (2013), van Mol (2013, van Mol and Timmerman (2013), Vargas-Silva (2013), and especially Blitz (2014) and Favell (2014).…”
Section: The Issue: the Need To Theorize Current Eu In-mobility Eu Inmentioning
confidence: 99%